The Book That Breathes New Life : Scriptural Authority and Biblical Theology - Brueggemann, Walter (Book collections on Project MUSE., 2011)
The purpose of this collection of Brueggemann's essays is to bring to the fore a much more extensive critical engagement on his part with the current discussion about the Old Testament, its character, its authority, its theology, and especially its God ... Readers of these essays who think they may have grasped what Brueggemann has to say about the theology of the Old Testament from reading his magnum opus will find that he is still thinking, still listening, and still helping us understand the scriptures of Israel and the church at an ever deeper level.